The moderating role of conscientiousness and gender in the relationship between perceived family atmosphere and academic performance in students from the city of Babylon, Iraq - Hussein Obeid Al-Soltani, Maryam; Mehdad, Ali; Oibed Al-Marshidi , Emad Hussein; Aghaee Jeshvaghani, Asghar (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The present research aimed to determine the moderating role of conscientiousness and gender in the relationship between perceived family atmosphere and academic performance.Methods and Materials:  The research method was correlational, utilizing hierarchical regression analysis, with the population comprising all students from the University of Babylon in Iraq, among whom 258 were conveniently selected. Data were collected using the Family Atmosphere Perception Questionnaire (Ryan et al., 1996), the Conscientiousness Questionnaire (Costa & McCrae, 2008), and students' academic averages and were analyzed using Pearson's correlation coefficient and hierarchical regression analysis through SPSS software version 26.Findings:  Results showed that there is a positive and significant relationship between perceived family atmosphere in both dimensions of parent-child and mother-child relationships with conscientiousness and academic performance, and between conscientiousness and academic performance (p